Perlindungan Hukum bagi Konsumen terhadap Klausula Baku dalam Transaksi E-Commerce Berdasarkan Undang-Undang Perlindungan Konsumen (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2026)
This research aims to analyze legal protection for consumers related to the use of standard clauses in e-commerce transactions in Indonesia. The rapid growth of the digital economy has encouraged the widespread application of “take-it-or-leave-it” contracts, which often include exoneration clauses that place consumers in a disadvantaged position. This study employs a normative legal research method using a statutory approach to examine the conformity of such clauses with existing consumer protection regulations. The findings reveal that many digital platforms continue to apply standard clauses that unilaterally transfer liability to consumers, which contradicts Article 18 of Law Number 8 of 1999 concerning Consumer Protection. As a result, these clauses are legally invalid and have no binding force. Consumer legal protection is implemented through preventive measures in the form of government supervision of business actors, as well as repressive measures through legal remedies and dispute resolution mechanisms provided by the Consumer Dispute Resolution Agency (BPSK). These mechanisms aim to ensure fairness and balance of interests between business actors and consumers in e-commerce transactions.